The temporal dimension of gender inequality in academia - Toren, Nina [Verfasser] (My University, 1993)
"This paper examines gender inequality in academic careers by applying Merton's concept of 'socially expected durations' (SEDs). Women's relatively slower advancement along the academic hierarchy has been traditionally attributed to their traits and constraints. The concept of SED shifts attention from the individual to the organizational level, and the actual and expected augmented durations between promotions for women are viewed as part of the structural arrangements of academic institutions and their culture. It is argued that because of the distinct characteristics of academic careers, time-in-rank is an important dimension distinguisching among otherwise very uniform occupational roles an career patterns. The implications of conceptualizing career discrepancies in terms of socially expected durations are discussed." (author's abstract, IAB-Doku) ((en)) Die zeitliche Dimension von akademischen Berufsverläufen wird in diesem Beitrag als Erklärungsansatz für die Ungleichheit zwischen den Geschlechtern beim beruflichen Aufstieg untersucht. In diesem Konzept wird die Aufmerksamkeit von der Person auf das organisatorische Umfeld gelenkt und die bei Frauen erwartete längere Zeitspanne zwischen den einzelnen Karriereschritten wird als Bestandteil der Strukturen von akademischen Institutionen und der akademischen Kultur angesehen. Die Autorin untermauert ihre Analyse mit empirischen Ergebnissen über die israelischen Universitäten und Beispielen von ähnlichen Strukturen in amerikanischen und europäischen Hochschulen. (IAB)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.4.1 Bildungs- und Berufswege; G 2.4.4 Biografiegestaltung; P 2.6 Hochschulabsolventen; P 1.3 Frauen; P 2.1.5 Fachhochschul- und Hochschulreife; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Berufsverlauf; Beruflicher Aufstieg; Dauer; Akademiker; Frauen; Frauen in Einzelberufen; Frauenarbeit; Hochschule; Berufsproblem; Ungleichheit; Geschlechtsspezifische Faktoren